Project management education in metallurgical companies in the Czech Republic - Košťálová, Jana; Bednaříková, Marie; Paták, Michal (My University, 2018)
The paper focuses on the issue of project management education as the tool of positive influence on the success of project implementation in corporate practice. The aim of the authors is to identify the ways of training project managers, project team members and top management members in project management on the basis of interviews with human resources managers of metallurgical companies in the Czech Republic. Based on the findings, recommendations of appropriate measures are formulated at the end of the paper to improve the situation in the area of project management education in metallurgical companies.
Vzdělávání v oblasti projektového řízení v metalurgických firmách v České republice
Keywords: project management education; project management information system; hard project management skills; soft project management skills; metallurgical industry; vzdělávání v projektovém řízení; informační systém na podporu projektového řízení; základní znalosti projektového řízení; soft skills v projektovém řízení; metalurgické firmy